2018
DOI: 10.3389/fphar.2018.01310
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins in the Management of Metabolic Syndrome: A Pharmacological and Biopharmaceutical Review

Abstract: The term “metabolic syndrome” (MetS) refers to a combination of diabetes, high blood pressure, and obesity. The origin of MetS includes a combination of multiple factors, such as sedentary lifestyle, unhealthy diet choice, and genetic factors. MetS is highly prevalent and adversely affects the general population by elevating risk of cardiovascular complications, organ failure, and much other pathology associated with late-stage diabetes. Anthocyanins (ANTs) are health-promoting bioactive compounds belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 182 publications
1
61
0
Order By: Relevance
“…The effects of anthocyanin supplementation on the body weight remain controversial [72,73]. However, our data confirmed that anthocyanins are health-promoting bioactive compounds [74]. Several studies have shown that phytocompounds found in fruits and vegetables have beneficial health effects, such as prevention of cancer, cardiovascular diseases, and obesity [75].…”
Section: Discussionsupporting
confidence: 59%
“…The effects of anthocyanin supplementation on the body weight remain controversial [72,73]. However, our data confirmed that anthocyanins are health-promoting bioactive compounds [74]. Several studies have shown that phytocompounds found in fruits and vegetables have beneficial health effects, such as prevention of cancer, cardiovascular diseases, and obesity [75].…”
Section: Discussionsupporting
confidence: 59%
“…Hence, we assumed that anthocyanins in RRB might be responsible for the increase in plasma antioxidant capacity. It has been reported that cyanidin-3-glucoside and peonidin-3-glucoside, the major anthocyanin in RRB, act as a natural antioxidant with high reactivity toward reactive oxygen species (ROS) because of its capability to donate hydrogen atoms or transfer electron from several hydroxyl groups to free radicals and unpaired electrons [30]. However, increases in plasma antioxidant capacity might be accompanied with other bioactive polyphenols in RRB.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins improve cardiovascular health, as shown by epidemiological studies leading to clinical studies showing improved surrogate markers of cardiovascular health, such as hypertension, lipid profiles and endothelial function with increased effects in overweight individuals [26]. Thus, anthocyanins are important in the potential prevention and reversal of metabolic syndrome, including obesity and inflammation [27,28]. These clinical studies have been supported by animal studies, including our reports in the same model as this study on purple carrots, Queen Garnet plums, purple maize and chokeberries [13][14][15].…”
Section: Discussionmentioning
confidence: 99%